2007
DOI: 10.1002/jat.1196
|View full text |Cite
|
Sign up to set email alerts
|

The effects of erdosteine, N‐acetylcysteine and vitamin E on nicotine‐induced apoptosis of cardiac cells

Abstract: This study was conducted to investigate the frequency of apoptosis in rat cardiomyocytes after intratraperitoneal nicotine injection, in order to examine the roles of inflammatory markers [myeloperoxidase (MPO) and tumor necrosis factor alpha (TNF-alpha)] in nicotine-induced cardiac damage and to determine the protective effects of three known antioxidant agents (N-acetylcysteine (NAC), erdosteine and vitamin E) on nicotine toxicity in the heart. Female Wistar rats were divided into seven groups, each composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several lines of evidence have now reported that nicotine has pro-inflammatory actions in the cardiovascular system. In rats, nicotine administration for 21 days caused significant up-regulation of TNFα and myeloperoxidase accumulation in heart tissues (Demiralay et al, 2007). Nicotine also increased gene expression of TNFα and inducible nitric oxide synthase in mouse peritoneal macrophages and RAW264.6 macrophages in vitro (Lau et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have now reported that nicotine has pro-inflammatory actions in the cardiovascular system. In rats, nicotine administration for 21 days caused significant up-regulation of TNFα and myeloperoxidase accumulation in heart tissues (Demiralay et al, 2007). Nicotine also increased gene expression of TNFα and inducible nitric oxide synthase in mouse peritoneal macrophages and RAW264.6 macrophages in vitro (Lau et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been broadly implicated as a major cause of nicotine-induced cardiovascular abnormalities both in vivo and in vitro. Indeed, supplementation with exogenous antioxidants such as vitamin E orally as well as through metallothionein overexpression; effectively prevented nicotine-induced cardiac damage in these animal models (Demiralay et al, 2007;Erat et al, 2007;Gumustekin et al, 2010;Hu et al, 2011). Although it is suggested that nicotine-induced upregulation of reactive oxygen species (ROS) production drives cardiac hypertrophy, fibrosis, and inflammation upon chronic exposure (Hu et al, 2011;Ramalingam et al, 2016), limited data is available to describe precise mechanisms underlying nicotine-induced oxidative stress and cardiac dysfunction in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…To test the effect of oxidative stress on fetal hearts, N-acetylcysteine (NAC; 10 mg/mL, N ¼ 4) was administered in the drinking water in the presence/absence of nicotine at a dose (496 + 37 mg/kg per d) that was effective (300-500 mg/kg) in inhibiting oxidative stress. [30][31][32] N-Acetylcysteine is an endogenous substrate in glutathione synthesis, a natural antioxidant via the glutathione pathway, 33 and considered safe during pregnancy. 34 At near term, pregnant animals were anesthetized with ketamine (80 mg/kg) and xylazine (1 mg/kg) and administered a subcutaneous injection of lidocaine prior to receiving an abdominal incision.…”
Section: Animal Modelmentioning
confidence: 99%
“…The incubation process was continued by incubation with primary anti-MPO antibody, biotinylated goat-mouse antibody and chromogenic substrate. Following this process, the sections were counterstained with hemotoxylin-eosin (8). The ration of the stained MPO in the cytoplasm of the neutrophils was evaluated by means of intensity and frequency of staining (26).…”
Section: Histopathological Evaluationmentioning
confidence: 99%